Urgency of Theological Values and Modernization in Islamic Education: Perspective of the Qur'an and Hadith - Nur Fatimah; Taufik Rahman; Irwan Abdurrohman; Wiwin Suhada; Adang Hambali; Hasan Basri (Mauriduna : Journal of Islamic Studies, 2025)
The rapid flux of and the transformations in time marked by technological advances and modernization have a significant impact on the education system, including Islamic education. In the midst of the current of modernity, theological values derived from the Qur'an and Hadith are often marginalized, though both play a fundamental role in shaping learners' character and integrity. This study aimed to analyze the urgency of integrating Islamic theological values in modern education and to identify relevant approaches based on Qur'anic and Hadith perspectives. This study employed a qualitative method with a library research approach and thematic analysis of Qur'anic verses and hadiths related to education, theological values, and the challenges of modernization. The results of the study indicated that theological values such as monotheism, morality, and social responsibility provide strong spiritual resilience in facing moral crises and the decadence of value due to modernization. The integration of these values in the curriculum and practice of Islamic education not only strengthens the foundation of faith, but also cultivates individuals who are religious, critical, and adaptive. The novelty of this study lay in the affirmation of the need for a harmonious synthesis between theological teachings and the demands of modernity in contemporary Islamic education. The implication is that educational policymakers and practitioners must redesign a pedagogical approach that is responsive to the times without losing its theological roots.